2004
DOI: 10.1074/jbc.m314331200
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenol and Curcumin Inversely Regulate Human Involucrin Promoter Activity via Opposing Effects on CCAAT/Enhancer-binding Protein Function

Abstract: Antioxidants are important candidate agents for the prevention of disease. However, the possibility that different antioxidants may produce opposing effects in tissues has not been adequately explored. We have reported previously that (؊)-epigallocatechin-3-gallate (EGCG), a green tea polyphenol antioxidant, stimulates expression of the keratinocyte differentiation marker, involucrin (hINV), via a Ras, MEKK1, MEK3, p38␦ signaling cascade (Balasubramanian, S., Efimova, T., and Eckert, R. L. (2002) J. Biol. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 60 publications
6
76
0
Order By: Relevance
“…Keratinocytes were transfected with an involucrin promoter-luciferase reporter plasmid, pINV-241, in which the proximal hINV promoter is linked to luciferase (Balasubramanian et al, 2002;Balasubramanian and Eckert, 2004). Our studies showed that treatment with EGCG for 24 h activates the human involucrin promoter reporter plasmid, pINV-241.…”
Section: Chemopreventive Agents Differentially Regulate Hinv Gene Expmentioning
confidence: 83%
See 4 more Smart Citations
“…Keratinocytes were transfected with an involucrin promoter-luciferase reporter plasmid, pINV-241, in which the proximal hINV promoter is linked to luciferase (Balasubramanian et al, 2002;Balasubramanian and Eckert, 2004). Our studies showed that treatment with EGCG for 24 h activates the human involucrin promoter reporter plasmid, pINV-241.…”
Section: Chemopreventive Agents Differentially Regulate Hinv Gene Expmentioning
confidence: 83%
“…Immunoblot studies confirm that EGCG enhances the level of the AP1 factors including Fra-1, Fra-2, c-fos, fosB, Jun-B, Jun-D and c-jun. Moreover, gel supershift analysis reveals that EGCG increases binding of Fra-1 and Jun-D to the hINV promoter AP1-1 site (Balasubramanian et al, 2002;Balasubramanian and Eckert, 2004;.…”
Section: Regulation Of Ap 1 Transcription Factor Functionmentioning
confidence: 97%
See 3 more Smart Citations